Lowering the density of dislocations in heteroepitaxial III-nitride layers: Effect of sapphire substrate treatment (review) - Parphenyuk, P.V.; Evtukh, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
In this paper, different methods for lowering the dislocation density such as incorporation of the buffer layers, substrate patterning and nitridation, silan-ammonia treatment are reviewed and compared. Advantages and limitations of these methods as well as a specific mechanism to reduce the dislocation amount are discussed. Usually, high densities of threading dislocations within the range 10¹⁰…10¹¹ cm⁻² are present in typical thin nitride films that are directly grown on sapphire substrate. Using these methods for substrate preparation, the density of dislocations can be reduced to the value 1·10⁷ cm⁻². An important process that enables to obtain the high-quality GaN layers with the low dislocation density is patterning the sapphire substrate. The dislocation density of these substrates depends on the pattern shape and orientation of patterned strips on cplane sapphire. Layers of GaN grown on a cone-shaped pattern have the lowest dislocation density. In addition, patterning the sapphire substrate increases the external quantum efficiency of radiative structures and reduces the mechanical stresses in the nitride layers.